Movement pattern specificity advantages of using pulling movements - Gattone, M.; Schilling, B.; Pierce, K.; Byrd, R. (coachesinfo.com, 2009)
Movement pattern specificity should not be underestimated as to its importance. The vertical jump can be used as an example. Studies have noted both kinetic and kinematic similarities between the vertical jump and pulling movements (Garhammer and Gregor 1992, Canavan et al. 1996. Thus the fundamental pattern of movement for a snatch or clean pull and a vertical jump with a two-leg take-off are quite similar. Basically the pulling movement is a jump with weights, which provides an overload. If movement pattern similarities are reasonable and a reasonable overload is afforded then it can be assumed that athletes consistently using pulling movements, as part of their training would have an excellent vertical jump. Evidence for this assumption can be found in both observation and research. For example, the vertical jumps of weightlifterÕs have been shown to be superior when compared to other athletes such as American football players and track and field athletes (Stone 1991).